Nutritional profile, protein quality, and biological value of raw and roasted cashew kernels (Anacardium occidentale) grown in southwest Nigeria - Olatidoye, Olawale Paul (Array, 2020)
Cashew kernels are one of the most concentrated food products due to their fat and protein content and they are used in puddings and bakery products, hence the determination of their protein quality is an important nutritional factor in dietary protein requirements. Therefore, the study aimed at evaluating the effect of roasting conditions on the protein quality of cashew kernels at the temperature of 100–160 °C and time (20–60 min), and then analysing for the amino acid profile by GC-FID; protein predicted efficiency ratio (P-PER), essential amino acid index (EAAI), and the Isoelectric point (pI). About 2.0 kg of dried cashew kernels used were defatted using chloroform/methanol (2:1/v/v) as the extraction solvent and then analysed using standard methods. The results showed that seventeen amino acids were present in cashew nuts, where glutamic acid (15.27g/100gN); aspartic acid (12.20g/100gN); lysine (6.09g/100g N), and phenylalanine (5.06g/100g N) were predominant. Eight essential amino acids were present in cashew kernels, the highest value of 7.33g/100g were for lysine (6.09g/100gN); 1.70g/100gN (histidine); 3.42g/100gN (threonine); 3.63g/100gN (valine); 3.57 g/100gN (isoleucine); 7.33g/100gN (leucine); and 5.06g/100gN (phenylalanine). Roasting reduced the lysine content by 18.4%, phenylalanine by 12.06%, and aspartic acid by 41.4% at 160°C for 60 min, while serine (58.9%); glutamic acid (19.7%); arginine (47.4%), and histidine (115.9%) were increased, suggesting that cashew nuts contain high quality protein. P-PER results were 2.57 (raw), 171-2.61 (roasted); EAAI is 1.55(raw) and 1.38-1.55 (roasted), BV% is 76.15 (raw) and 67.61-76.89 (roasted); the Isoelectric points were 4.65 (raw) and 3.87- 4.54 (roasted), The Leu/Ileu ratio was 2.12 (raw) and 2.01-2.67 (roasted). It was concluded that the heat treatment used does not significantly affect the amino acid profile of cashew kernels, thus preserving their nutritional quality.